Pemahaman Kode Etik Akuntan, Love of Money, Religiusitas, Equity Sensitivity Pada Persepsi Etis Mahasiswa Akuntansi - Devi, Laksmi; Anggara, I Wayan Gde Wahyu Purna (E-Jurnal Akuntansi; Vol 32 No 12 (2022), 2022)
The research was conducted with the aim of knowing the effect of understanding the accounting profession's code of ethics, love of money, religiosity and equity sensitivity on the ethical perceptions of accounting students. The population in the study were undergraduate students of the accounting study program class of 2018 at the University in Bali with a total of 2,220 people. The sample in this study were 138 people using the probability sampling technique, namely the random sampling method. Data analysis technique used in multiple linear regression research. The results showed that understanding of the accounting profession's code of ethics, religiosity, and equity sensitivity had a positive effect on accounting students' ethical perceptions. Meanwhile, the love of money has a negative effect on ethical perceptions of accounting students. Keywords: The Accounting Profession’s Code Of Ethics; Love Of Money; Religiosity; Equity Sensitivity; Ethical Perception Of Accounting Students.